2002
DOI: 10.1295/polymj.34.138
|View full text |Cite
|
Sign up to set email alerts
|

Controlled/“Living” Radical Ring-Opening Polymerization of 5,6-Benzo-2-Methylene-1,3-Dioxepane Based on Reversible Addition-Fragmentation Chain Transfer Mechanism

Abstract: ABSTRACT:The radical ring-opening polymerization of 5,6-benzo-2-methylene-1,3-dioxepane (BMDO) was performed in the presence of 1-(ethoxycarbonyl)prop-1-yl-dithiobenzoate (EPDTB) and dicumyl peroxide (DCP). The completely ring-opening polymerization of BMDO via reversible addition-fragmentation transfer mechanism was proved to be controlled by the following experimental evidences: the straight line of ln ([M] 0 /[M] t ) vs. polymerization time; linear increase of molecular weight with increasing conversion and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…33,34 However, with the exception of less activated monomers (LAMs) such as VAc, the reactivity ratios for these copolymerizations indicate that final polymer compositions are more gradient-like or blocky, not statistical. 17,25,29,35 Control of polymerizations incorporating CKAs has also been attempted through reversible-deactivation radical polymerization (RDRP) techniques such as Nitroxide-Mediated Polymerization (NMP), 19,36 Atom Transfer Radical Polymerization (ATRP), [37][38][39] and Reversible Addition-Fragmentation Chain-Transfer Polymerization/Macromolecular Design by Interchange of Xanthates (RAFT/MADIX) 40 but there are only a handful of examples where these techniques have been used to control copolymerizations with MDO. Using BlocBuilder MA alkoxyamine initiator (SG1) to mediate the copolymerization of PEGMA or MMA, AN, and MDO, Delplace et al have demonstrated control with final dispersities, Đ M , <1.4.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 However, with the exception of less activated monomers (LAMs) such as VAc, the reactivity ratios for these copolymerizations indicate that final polymer compositions are more gradient-like or blocky, not statistical. 17,25,29,35 Control of polymerizations incorporating CKAs has also been attempted through reversible-deactivation radical polymerization (RDRP) techniques such as Nitroxide-Mediated Polymerization (NMP), 19,36 Atom Transfer Radical Polymerization (ATRP), [37][38][39] and Reversible Addition-Fragmentation Chain-Transfer Polymerization/Macromolecular Design by Interchange of Xanthates (RAFT/MADIX) 40 but there are only a handful of examples where these techniques have been used to control copolymerizations with MDO. Using BlocBuilder MA alkoxyamine initiator (SG1) to mediate the copolymerization of PEGMA or MMA, AN, and MDO, Delplace et al have demonstrated control with final dispersities, Đ M , <1.4.…”
Section: Introductionmentioning
confidence: 99%
“…Radical polymerization of MDO in the presence of a stable free radical (TEMPO) was shown to yield a ring‐opened aliphatic polyester with narrow molecular weight distributions 21, 22. The cyclic ketene acetal 5,6‐benzo‐2‐methylene‐1,3‐dioxepane has been homopolymerized by reversible addition‐fragmentation chain transfer polymerization23 and homo‐24, 25 and copolymerized with vinyl monomers26, 27 by atom transfer radical polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…BMDO [76] -20 [44] S, [14,44,46,77] MA, [44] BA, [13,44] S-b-DMA, [14,77] S-b-SMe, [14,77] MMA-b-S, [9] (MMA), [44] DMA, [14] S-MAH, [51,79,80] (AMS-MAH) [51] NIPAM, [78] S, [9,14] MMA [9] (continued) …”
mentioning
confidence: 99%